Effect of N-doped carbon coatings on the durability of highly loaded platinum and alloy catalysts with different carbon supports for polymer electrolyte membrane fuel cells. (24th May 2018) - Ahn, Chi-Yeong; Hwang, Wonchan; Lee, Hyunjoon; Kim, Sungjun; Park, Ji Eun; Kim, Ok-Hee; Her, Min; Cho, Yong-Hun; Sung, Yung-Eun
Abstract: An ideal oxygen reduction catalyst for use in fuel cells should exhibit both long-term durability and high activity. In this study, to increase the durability of highly loaded platinum- and platinum-nickel alloy catalysts possessing different types of carbon supports, a nitrogen-doped carbon shell was introduced on the catalyst surface through dopamine coating. As the catalyst surfaces were altered following shell formation, the ionomer contents of the catalyst inks were adjusted to optimise the three-phase boundary formation. Single cell tests were then conducted on these inks by applying them in a membrane electrolyte assembly. Furthermore, to confirm the durability of the catalysts under accelerated conditions, the operation was continued for 200 h at 70 °C and at a relative humidity of 100%. Transmission electron microscopy and electrochemical analysis were conducted before and after the durability tests, and the observed phenomena were discussed for catalysts bearing different types of carbon supports. Graphical abstract: Highlights: Nitrogen-doped carbon shell by dopamine coating is introduced to highly-loaded Pt and PtNi alloy catalysts. Pt and PtNi catalysts are supported on carbon black and heat-treated carbon, respectively. Performance and durability were improved by applying a Pt-alloy catalyst in combination with a N-doped carbon shell.